Revision of the genus Placospongia (Porifera, Demospongiae, Hadromerida, Placospongiidae) in the Indo-West Pacific - Becking, L.E. (ZooKeys, 2013)
Species of the genus Placospongia are common within the tropical Indo-West Pacific, demonstrating a wide variety of colors and either branching or encrusting growth forms. A revision of Indo-West Pacific Placospongia was undertaken based on a redescription of the holotypes of species of Placospongia from the Indian Ocean and Western Pacific and an examination of an additional 103 specimens of Placospongia ssp. collected from Indonesia (including Vosmaer and Vernhout 1902 material), Seychelles, India, Singapore and Micronesia. One mitochondrial (COI) and one nuclear (ITS) marker were subsequently used to differentiate species. All Placospongia species are characterized by selenasters and tylostyles in two size classes. The combination of microsclere diversity and morphology as well as megasclere size were shown to be informative morphometric characters, supported by molecular evidence. Live coloration and growth form is shown to be unreliable for diagnoses. The study of holotypes found that P. mixta is a valid species and that two genus transfers are necessary: Geodinella anthosigma is a Placospongia and P. labyrinthica is a Geodia. A new species is also described from an anchialine pool in Indonesia, Placospongia santodomingoae sp. n.; bringing the total fauna of Placospongia species in the Indo-West Pacific to five: Placospongia anthosigma, Placospongia carinata, Placospongia mixta, Placospongia melobesioides, and Placospongia santodomingoae sp. n. An identification key is given. Two additional species, possibly morphologically cryptic, have been identified by molecular markers.